γ‐Secretase inhibitors in cancer clinical trials are pharmacologically and functionally distinct - Yong Ran; Fokhrul Hossain; Antonio Pannuti; Christian B Lessard; Gabriela Z Ladd; Joo In Jung; Lisa M Minter; Barbara A Osborne; Lucio Miele; Todd E Golde (EMBO Molecular Medicine, 2017)
Abstract γ‐Secretase inhibitors (GSIs) are being actively repurposed as cancer therapeutics based on the premise that inhibition of NOTCH1 signaling in select cancers is therapeutic. Using novel assays to probe effects of GSIs against a broader panel of substrates, we demonstrate that clinical GSIs are pharmacologically distinct. GSIs show differential profiles of inhibition of the various NOTCH substrates, with some enhancing cleavage of other NOTCH substrates at concentrations where NOTCH1 cleavage is inhibited. Several GSIs are also potent inhibitors of select signal peptide peptidase (SPP/SPPL) family members. Extending these findings to mammosphere inhibition assays in triple‐negative breast cancer lines, we establish that these GSIs have different functional effects. We also demonstrate that the processive γ‐secretase cleavage pattern established for amyloid precursor protein (APP) occurs in multiple substrates and that potentiation of γ‐secretase cleavage is attributable to a direct action of low concentrations of GSIs on γ‐secretase. Such data definitively demonstrate that the clinical GSIs are not biological equivalents, and provide an important framework to evaluate results from ongoing and completed human trials with these compounds.